2016
DOI: 10.1002/chem.201603823
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of Dynamic Vibrational Spectroscopy to Determine the Molecular Structure and Dynamics of Ferrocene

Abstract: Molecular distortion of dynamic molecules gives a clear signature in the vibrational spectra, which can be modeled to give estimates of the energy barrier and the sensitivity of the frequencies of the vibrational modes to the reaction coordinate. The reaction coordinate method (RCM) utilizes ab initio-calculated spectra of the molecule in its ground and transition states together with their relative energies to predict the temperature dependence of the vibrational spectra. DFT-calculated spectra of the eclipse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…5 Such the discovery of Fc conformers stimulates a number of significant experimental and theoretical studies. 3,8,9,20,26 For example, a recent highly accurate X-ray absorption fine structures (XAFS) study of ferrocene (Fc) confirmed a near-eclipsed D5h geometry at low-temperature, 7,9 in agreement with our earlier theoretical results. 5 The recent self-consistent temperature and environment sensitive IR spectral study of Fc, by a series of Synchrotron-based high-resolution IR spectral measurements provided insight on the electronic structure changes of Fc with temperature.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…5 Such the discovery of Fc conformers stimulates a number of significant experimental and theoretical studies. 3,8,9,20,26 For example, a recent highly accurate X-ray absorption fine structures (XAFS) study of ferrocene (Fc) confirmed a near-eclipsed D5h geometry at low-temperature, 7,9 in agreement with our earlier theoretical results. 5 The recent self-consistent temperature and environment sensitive IR spectral study of Fc, by a series of Synchrotron-based high-resolution IR spectral measurements provided insight on the electronic structure changes of Fc with temperature.…”
Section: Introductionsupporting
confidence: 87%
“…Unfortunately, no study has been able to obtain such conclusive properties until a recent theory led study of Fc using infrared (IR) spectroscopy. 5 Despite significant advances in experimental techniques such as XAFS which has been employed to study Fc, 7 and the first comprehensive study of Fc dynamics based on theory and a series of theory-guided infrared (IR) spectral measurements, 8 it concluded that the Fc is in eclipsed form at low temperature (e.g. 0 K) and becomes a mixture of both conformers at higher temperatures such as room temperature 300 K. 7,9 Ferrocene has been studied extensively in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] A closer inspection of a number Fc IR measurements, in particular, the IR measurements in gas phase and in carbon tetrachloride (CCl4) solvent of Lippincott and Nelson, [38] found that the shape of this IR band (ν1, ν2) of Fc is opposite in gas phase (393 K) and in CCl4 solution (298 K). That is, this band in gas phase is measured as I(ν2)<I(ν1) [34,40] (opposite to the calculated), [8] whereas in CCl4 solution, the same band is given by I(ν2)>I(ν1), [34,40] (the same as the calculated). In order to understand this issue, a series of theory guided temperature dependent IR spectral measurements of Fc in gas phase was designed and performed.…”
Section: Lippincottmentioning
confidence: 66%
“…[15] As shown in Table 1, the IR spectral band (ν1, ν2) splitting indicates the dominance of eclipsed Fc conformer. [8] However, the intensities (shape) of the measured Fc IR spectra in gas phase are given by I(ν2)<I(ν1) [34,40] (see Figure 2), whereas the calculation indicates the opposite, I(ν2)>I(ν1) in gas phase. [8] A closer inspection of a number Fc IR measurements, in particular, the IR measurements in gas phase and in carbon tetrachloride (CCl4) solvent of Lippincott and Nelson, [38] found that the shape of this IR band (ν1, ν2) of Fc is opposite in gas phase (393 K) and in CCl4 solution (298 K).…”
Section: Lippincottmentioning
confidence: 95%